2019
DOI: 10.20882/adicciones.1145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la adaptación de los ítems de consumo del AUDIT para mejor el cribado de Binge Drinking en universitarios

Abstract: Evaluación de la adaptación de los ítems de consumo del AUDIT para mejor el cribado de Binge Drinking en universitarios

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This study has tested whether reformulation of items A2r and A3r (AR2i), and new combination that includes the two previous items plus 4, 8, and 9 are a suitable alternative for classifying young BD individuals. The results confirm that both versions obtain better sensitivity and specificity values than the traditional scales (AUDIT and AUDIT-C), being even higher than those of previous studies that tested AR2i Blank et al, 2015;García et al, 2016;Motos et al, 2019) and than those that used other combinations of items (McCambridge & Thomas, 2009). With a cut-off point of ≥ 3, only 1.7% of BD females are incorrectly classified.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This study has tested whether reformulation of items A2r and A3r (AR2i), and new combination that includes the two previous items plus 4, 8, and 9 are a suitable alternative for classifying young BD individuals. The results confirm that both versions obtain better sensitivity and specificity values than the traditional scales (AUDIT and AUDIT-C), being even higher than those of previous studies that tested AR2i Blank et al, 2015;García et al, 2016;Motos et al, 2019) and than those that used other combinations of items (McCambridge & Thomas, 2009). With a cut-off point of ≥ 3, only 1.7% of BD females are incorrectly classified.…”
Section: Discussionsupporting
confidence: 80%
“…Previous research indicates the importance of addressing the different levels of severity involved in the practice of this consumption behaviour (Cortés et al, 2016;Patrick et al, 2013;Read et al, 2008) due to the more or less evident consequences it has on a young person. Therefore, this paper opens up the possibility of new lines of research focused on checking the relevance of AR2i and the new combination of AUDIT items (A2r, A3r, 4, 8, and 9) among BD individuals of varying intensities Motos et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 According to the National Institute on Alcohol Abuse and Alcoholism (NIAAA), the definition of binge drinking is typically 5 drinks for men and 4 drinks for women during a 2-hour session, resulting in a blood alcohol level greater than 80 mg/dl. 10 In experimental studies, alcohol given acutely or in a binge-like paradigm resulted in worse cognitive performance, impairment in spatial processing and decreased recognition memory in rats. 11 -13 Furthermore, in a rat model of TBI and binge alcohol, our group has shown that skilled sensorimotor recovery was worse in alcohol-treated animals.…”
Section: Introductionmentioning
confidence: 99%